Spontaneous discharge from Gartner’s duct cyst in a perimenopausal woman: a rare case - Rajendran, Sathiyakala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Gartner’s duct cyst which arises from the remnants of the distal part of Wolffian duct is rare, especially in a perimenopausal woman. Hereby, presenting a case of huge Gartner’s duct cyst with spontaneous discharge in a perimenopausal woman. A 40 year old woman, who is having mass descending per vaginum for the past 2 years and discharge from the mass for the past one week, is diagnosed to have a Gartner’s duct cyst in the right lateral vaginal wall. There was mucous discharge from the cyst through a pin hole opening in the vaginal wall covering the cyst. Under antibiotic cover, the cyst was excised completely. The patient was advised follow up.